Memorandum of Understanding between Military Institute of Science and Technology (MIST) and Brac University (2013) - Brac University; Military Institute of Science and Technology (MIST) (Brac University and Military Institute of Science and Technology (MIST), 2019)
The agreement made between Military Institute of Science and Technology (MIST) and Brac University for installation, setup, and maintenance support of "Integrated library management System (implementation of,Koha (Library Management Software), Dspace (Digital institutional repository), Vufind (Discovery Tool) and Drupal.